Técnicas e instrumentos de evaluación para la retroalimentación del proceso enseñanza aprendizaje de los estudiantes de tercer año de educación básica de la escuela Otto Arosemena Gómez de la ciudad de Latacunga, parroquia La Matriz, durante el período 2014-2015 - Bombón Toapanta, Betty Carolina (2015)
The research goal was to optimize the techniques and assessment tools’ use for academic feedback. This is an answer to the problem: “the lack of technical and assessment tools for the feedback system. The methods applied were analytical and inductive. Analytical Method was used in analysis and interpretation of research results. Inductive was used in research findings’ formulation. The research results show confusion between assessment techniques and instruments with academic feedback. The test is the most widely technique used in this kind of process. The survey and interview are used for administrative purposes and it is not for educational purposes….